Clostridium botulinum type C in the Mersey estuary. - Smith, G. R. (Cambridge University Press, 1982)
Nineteen of 98 samples of mud or sand taken from the Mersey estuary in 1981 contained Clostridium botulinum type C, the organism almost always responsible for botulism in water birds. In the Dungeon and Score Bank areas, where many dead and dying birds were found during the period September-December 1979, almost half the samples contained type C. Most of the positive samples were essentially muddy rather than sandy. The findings do not prove that botulism contributed to the 1979 mortality but are nonetheless thought-provoking, particularly because type C--unlike type B--is by no means ubiquitous in Britain. Type B was present in 12.2% of samples from the Mersey estuary.